PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTS NEGERI 1 INDRAGIRI HILIR - Sari, Ade Irma; Armis, Armis; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a classroom action research that aims to improve the learning process and to increase mathematics achievement with applied learning model of Problem Based Learning. The subjects of this research was student of class VIII MTs Negeri 1 Indragiri Hilir in academic years 2018/2019, which are 28 students, consist of 13 boys and 15 girls. This research consisit of two cycles, each cycles has four stages, which are planning, implementation, observation, and reflection. The instruments in this research is learning devices and instruments of data collection. Data collected are teacher’s activities and students’ activities and students’ mathematics achievement. Data collection techniques in this research consist of observation techniques and mathematics achievement test techniques. The data of observation results were analyzed in descriptive narrative techniques, while the students mathematic tests were analyzed in descriptive statistical techniques. The result of data analysis show teacher’s and student’s activity have been done very well in cycle II and weakness/deficiency that happened less from cycle I to cycle II. Implementation of PBL model enables students to observe and understand problems and can collect information related to problems given by teachers. The Students mathematics learning outcomes also increased in quiz I and quiz II seen from the achievement of students' knowledge and skills and frequency distribution analysis. The results of this analysis indicate that the application of the PBL model can improve the learning process and improve students mathematics learning outcomes of students of grade VIII students of MTs Negeri 1 Indragiri Hilir in 2018/2019 academic year at Polyhedron form Material.Key Words: Mathematics Achievement, Problem Based Learning, Class Action Research